Cerium, Neodimium, and Lanthanum Leaching from Rare Earth Oxides (REO) using Hydrochloric Acid - Aulia, Muhammad Azmi; Kurniawan, Cepi; Setyadji, Moch. (Indonesian Journal of Chemical Science, 2021)
Rare earth metal hydroxide (REOH) is a mixture of the elements lanthanide, yttrium, and scandium produced from the processing of monazite sand. This mixture has benefits in the modern technology industry, especially elements of Ce, La, and Nd. Separation of Ce, La, and Nd from the mixture has been carried out, but it has several drawbacks with the large use of chemicals that have an impact on the environment from the results of their processing waste and the length of time it takes, so the best solution is needed to overcome it. The perfect solution in the process of separating Ce, La, and Nd from REOH is leaching. Leaching is the extraction of acids with bases to form salt and water. This research begins with the REOH calcination process at a temperature of 1000â° C for 2 hours to evaporate volatiles and decompose the compounds. The results of calcination were leached using hydrochloric acid with a concentration variation of 0.3-1.2 M, temperature 30-75 Â° C, a ratio of REO and solvent 1:5, and time variation of 5-20 minutes to optimize leaching efficiency. The results of leaching in residues were analyzed by XRF. The optimum leaching of the variation of the concentration of hydrochloric acid 1,2 M for 20 minutes resulted in the leaching efficiency of La and Nd respectively 33,297% dan 26,503%, and the leaching efficiency of Ce was 10,153% of the concentration of hydrochloric acid 0,9 M for 20 minutes. At a temperature variation of 75â° C and a time of 10 minutes, the leaching efficiency La and Ce were 55,87% dan 0,04%, respectively. The efficiency of Nd at 45â°C for 20 minutes was 26,93%.